Video games and metacognition in the classroom for the development of 21st century skills: a systematic review - Checa-Romero, Mirian; Gimenez-Lozano, José Miguel (Frontiers in Education, 2025)
IntroductionGame-based learning is a methodology that has gained importance in the world of education due to the benefits of implementing ICT in the classroom. Due to the intellectual and competence demands that some commercial video games promote, they can be very valuable tools to stimulate and promote metacognitive abilities in students. Therefore, this paper aimed to analyze the use of commercial video games in educational contexts and their impact on the development of metacognitive skills.MethodsFor the analysis of the study, a systematic review of the literature was carried out following the PRISMA statement. Specialized databases such as Scopus, WoS, PsyInfo, PubMed, SciELO, and Eric were consulted, which helped capture the essence of the problem between 2004 and 2024.ResultsThe review was then carried out on 10 selected articles. The results obtained show the following evidence: (a) commercial video games, together with the use of metacognitive strategies, enrich academic and social aspects as well as the metacognitive level, and (b) commercial video games are as effective in promoting metacognition as other more traditional methodologies or tools.DiscussionFinally, there is a need to rethink the implications of the use of video games in the classroom if we want students to acquire skills that will be essential to successfully respond to the demands and challenges of their academic and professional future.